Using the method for detection correlation pleyades association between indicators of cerebrovascular disease - Vysotska, O. V.; Rysovana, L. M.; Alekseienko, R. V. (My University, 2017)
In the present article, cerebrovascular pathology is characterized as a medical and social problem that occurs on a background of crisis in family relations. Using the method of correlation pleyades analyzed the link between indicators of psychological tests to detect the absence or presence of a crisis in the family. In this study, we compared groups of women living in families with a lack of crisis and families in crisis, and identified links pointing to relations between spouses, which improves the quality and timely delivery of necessary assistance in the correction of these relations. The results obtained in this study, the results show the importance of the prediction of family crisis to prevent cerebrovascular disease and may be useful for neurologists, psychotherapists and psychologists. У представленій статті цереброваскулярна патологія характеризується як медико-соціальна проблема, що вини-кає на тлі кризи в сімейних відносинах. З використанням методу кореляційних плеяд проаналізовані зв'язки між показ-никами психологічних тестів, що дозволяють виявляти відсутність або наявність кризи в родині. У ході даного дослі-дження було проведене порівняння груп жінок, що живуть у родинах з відсутністю кризи й у кризових родинах, а та-кож виявлені зв'язки, що вказують на відносини з чоловіками, що дозволяє підвищити якість і своєчасне надання необ-хідної допомоги в корекції цих відносин. Отримані в даному дослідженні результати свідчать про важливість прогно-зування сімейної кризи для попередження цереброваскулярної патології й можуть бути корисні для невропатологів, психотерапевтів і психологів. В представленной статье цереброваскулярная патология характеризуется как медико-социальная проблема, воз-никающая на фоне кризиса в семейных отношениях. С использованием метода корреляционных плеяд проанализированы связи между показателями психологических тестов, позволяющих выявлять отсутствие или наличие кризиса в семье. В ходе данного исследования было проведено сравнение групп женщин, живущих в семьях с отсутствием кризиса и в кри-зисных семьях, а также выявлены связи, указывающие на отношения между супругами, что позволяет повысить каче-ство и своевременное оказание необходимой помощи в коррекции этих отношений. Полученные в данном исследовании результаты, свидетельствуют о важности прогнозирования семейного кризиса для предупреждения цереброваскуляр-ной патологии и могут быть полезны для невропатологов, психотерапевтов и психологов.
Keywords: Correlation pleyada; family crisis; cerebrovascular disorders